New modified weight function for the dissipative force in the DPD method to increase the Schmidt number. (8th May 2015) - Yaghoubi, S.; Shirani, E.; Pishevar, A. R.; Afshar, Y.
Abstract: To simulate liquid fluid flows with high Schmidt numbers (Sc), one needs to use a modified version of the Dissipative Particle Dynamics (DPD) method. Recently the modifications made by others for the weight function of dissipative forces, enables DPD simulations for Sc, up to 10. In this paper, we introduce a different dissipative force weight function for DPD simulations that allows achieving a solution with higher values of Sc and improving the dynamic characteristics of the simulating fluid. Moreover, by reducing the energy of DPD particles, even higher values of Sc can be achieved. Finally, using the new proposed weight function and, the Sc values can reach up to 200.